2010
DOI: 10.1007/s10689-010-9380-3
|View full text |Cite
|
Sign up to set email alerts
|

Communicating genetic risk information within families: a review

Abstract: This review of family communication of genetic risk information addresses questions of what the functions and influences on communication are; what, who and how family members are told about genetic risk information; what the impact for counsellee, relative and relationships are; whether there are differences by gender and condition; and what theories and methodologies are used. A systematic search strategy identified peer-reviewed journal articles published 1985-2009 using a mixture of methodologies. A Narrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
140
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(156 citation statements)
references
References 43 publications
13
140
1
2
Order By: Relevance
“…This raises ethical issues for health professionals and services, as their degree of responsibility for ensuring relatives' awareness of their risks -and the extent to which they should be proactive in this task -have long been debated in genetic health care. 16,17 Previous reviews have been published on the process and outcomes of communication of genetic information within families, [18][19][20] including the communication between children and their parents, 21 the factors influencing patterns of intrafamilial communication and awareness, 22,23 and on the analysis of the communication between genetic specialists and patients. 24 However, to our knowledge there has been no systematic review of studies that have analysed how family communication of information about genetic risks is addressed in genetic counselling practice.…”
Section: Introductionmentioning
confidence: 99%
“…This raises ethical issues for health professionals and services, as their degree of responsibility for ensuring relatives' awareness of their risks -and the extent to which they should be proactive in this task -have long been debated in genetic health care. 16,17 Previous reviews have been published on the process and outcomes of communication of genetic information within families, [18][19][20] including the communication between children and their parents, 21 the factors influencing patterns of intrafamilial communication and awareness, 22,23 and on the analysis of the communication between genetic specialists and patients. 24 However, to our knowledge there has been no systematic review of studies that have analysed how family communication of information about genetic risks is addressed in genetic counselling practice.…”
Section: Introductionmentioning
confidence: 99%
“…Counselees indeed feel generally obliged to disclose genetic risk information to relatives [5][6][7]. However, they do not always succeed in correctly informing all relevant relatives [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that genetic risk information is often poorly understood and retained [21][22][23]. A lack of motivation may be due to the desire to protect the relative or oneself, e.g., from negative reactions by the relative [7]. Counselees may consider a relative to be too old or too emotionally fragile to burden them with genetic cancer information [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determination of the relevant factors which predispose to positive effects should be addressed in future research on the manner of telling, the information conveyed, and subsequent discussions about hereditary cancer. 1 Because previous research efforts have tended to focus on negative effects, 60 we suggest that studying positive and neutral effects is just as important. A better understanding of how BRCA1/2 testing can positively affect family dynamics may suggest strategies for genetic service providers to help individuals get the greatest benefit from their testing experience and relieve the burden of concern for those considering testing about the impact of family disclosure on relationships with close relatives.…”
Section: Discussionmentioning
confidence: 99%